Microplastic as an written composition in bottled water: Implications for waste management - Kurniawan, Aprilian (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Microplastics are the smallest particles of plastic measuring about 4.8 milliliters and are dangerous to the body due to the chemicals they contain, such as PCBs (Polychlorinated Biphenyls). Microplastics have been identified in various studies, both in aquatic and terrestrial environments, raising concerns about contamination in seafood, beverages (like beer), and more recently, bottled mineral water. Methods: This publication compiles and discusses currently available literature data on microplastic particles found in bottled mineral water. Findings: The discovery of microplastics in bottled mineral water highlights the widespread contamination of microplastics in consumable products, emphasizing the importance of water intake for supporting body metabolism. Conclusion: The identification of microplastics in bottled mineral water underscores the need for greater awareness of the dangers of microplastic contamination and its potential health risks. Novelty/Originality of this article: This article uniquely highlights the underexplored presence of microplastics in bottled mineral water, emphasizing the health risks associated with chemical contaminants like PCBs, and calls for increased awareness and regulatory measures to protect consumer safety.